Beyond the European Union Tobacco Products Directive: smokers' and recent quitters' support for further tobacco control measures (2016–2018). Issue 6 (16th March 2021) - Nogueira, Sarah O; Driezen, Pete; Fu, Marcela; Hitchman, Sara C; Tigova, Olena; Castellano, Yolanda; Kyriakos, Christina N; Zatoński, Mateusz Zygmunt; Mons, Ute; Quah, Anne C K; Demjén, Tibor; Trofor, Antigona Carmen; et al.
Abstract : Background: Several measures recommended by the WHO Framework Convention on Tobacco Control have not been implemented in the European Union, despite changes in the legislation such as the Tobacco Products Directive (TPD). This study aims to understand smokers' and recent quitters' levels of support for tobacco control measures that go beyond the TPD during and after its implementation. Methods: Data from wave 1 (2016, n=6011) and wave 2 (2018, n=6027) of the EUREST-PLUS International Tobacco Control Policy Evaluation Project Six European Countries Survey, a cohort of adult smokers in Germany, Greece, Hungary, Poland, Romania, Spain were used to estimate the level of support for seven different tobacco control measures, overall and by country. Results: In 2018, the highest support was for implementing measures to further regulate tobacco products (50.5%) and for holding tobacco companies accountable for the harm caused by smoking (48.8%). Additionally, in 2018, 40% of smokers and recent quitters supported a total ban on cigarettes and other tobacco products within ten years, if assistance to quit smoking is provided. Overall, support for tobacco control measures among smokers and recent quitters after the implementation of the TPD remained stable over time. Conclusion: There is considerable support among smokers and recent quitters for tobacco control measures that go beyond the current measures implemented. A significant percentage of smokers would support a ban on tobacco products in the future if the government provided assistance to quit smoking. This highlights the importance of implementing measures to increase smoking cessation in conjunction with other policies.